2014
DOI: 10.3791/51664
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for Conducting Rainfall Simulation to Study Soil Runoff

Abstract: Rainfall is a driving force for the transport of environmental contaminants from agricultural soils to surficial water bodies via surface runoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
(11 reference statements)
1
30
0
Order By: Relevance
“…Although there is extensive information regarding environmental P risk using indoor rainfall simulations, much less attention has been paid to assessing N losses from different N sources. To date, few studies evaluated the simultaneous risk of N and P transport from soils receiving organic and inorganic fertilizer sources (Hansen et al, 2007; Diaz et al, 2010; Kibet et al, 2014). The lack of research on this topic is largely due to the complexity of the mechanisms controlling N dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is extensive information regarding environmental P risk using indoor rainfall simulations, much less attention has been paid to assessing N losses from different N sources. To date, few studies evaluated the simultaneous risk of N and P transport from soils receiving organic and inorganic fertilizer sources (Hansen et al, 2007; Diaz et al, 2010; Kibet et al, 2014). The lack of research on this topic is largely due to the complexity of the mechanisms controlling N dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively low solubility of nutrients in heat‐treated biosolids has been reported by others (O'Connor and Sarkar, 1999). Obviously, the proportion of N lost in runoff and leachate depends largely on the interactions among several factors such as the amount of N applied, initial soil moisture conditions (Eghball and Gilley, 1999; Kibet et al, 2014), and the application method (Pote et al, 2003). Although the intrinsic characteristics of packed soil runoff boxes are often not representative of field conditions (i.e., hydrology of disturbed or homogenized soil) (Srinivasan et al, 2007), results from this study were expected to reflect extreme conditions where biosolids and fertilizer are surface applied to wet soils and subjected to intensive rainfall immediately after application.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it is critical to assemble comprehensive and long-term datasets to enable robust statistical analysis, facilitate comparisons, and detect long-term trends. There is also a need to standardize rainfall simulators and experimental protocols (Kibet et al, 2014) and provide for a better dissemination of collected information among researchers . This paper presents the results of 272 rainfall simulation experiments on small plots in semiarid rangelands of the southwestern USA.…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not find any studies that investigated the fate and transport of urea in the Coastal Plain (CP) and Piedmont (PM) regions of Maryland across landscapes that included agricultural soils and neighboring ecosystems. One rainfall simulator study investigated the potential for urea to move with overland flow across agricultural soil surfaces, but the urea runoff values were low, amounting to 0.1 to 0.5% of applied urea‐N (Kibet et al, 2014). In another study done under very high urea‐N loss conditions (13% slope and an application rate of 450 kg urea‐N ha −1 ), Moe et al (1968) found that only 0.5% of the applied urea was lost in surface runoff.…”
mentioning
confidence: 99%